(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Background: The main aim of PICU is the surveillance and support of vital organ function in critically-ill or injured children who are at risk for organ dysfunction. Children are the most precious beings in our lives, but they are very fragile and easily succumb to disease and can have life threatening attacks in minutes. Advances in knowledge and technology of medical science have dramatically improved the prognosis for the critically-ill children. The main goal of pediatric intensive care unit (PICU) is to significantly decrease the mortality.